MEKANISME PENYELESAIAN TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA SECARA HUKUM ADAT DI DESA BONIA HILISIMAETANO KECAMATAN MANIAMOLO KABUPATEN NIAS SELATAN - Markus Waoma (LPPM Universitas Nias Raya, 2024)
The mechanism of domestic violence is the process of resolving any act against someone, especially women, which results in physical, sexual, psychological misery or suffering, and/or domestic neglect including threats to commit acts, coercion, or unlawful deprivation of liberty within the scope of household. The aim of this research is to find out the mechanism for resolving criminal acts of domestic violence according to customary law in Bonia Hilisimaetano Village, Maniamolo District, South Nias Regency. The type of research used is sociological or empirical legal research, namely examining applicable legal provisions based on existing facts in a society. Data collection was carried out using primary data, secondary data and tertiary data. obtained from secondary legal materials. The data analysis used is qualitative data analysis. Analyzing qualitative data is done concurrently with the process of gathering data. The research findings and discussion lead to the conclusion that Bonia Hilisimaetano Village, Maniamolo District, South Nias Regency, has a customary law-based mechanism for resolving criminal acts of domestic violence. This mechanism involves deliberation in the village, known locally as Orahu in Nias, with the village government inviting various parties, including the BPD, LAD (Fa'asiulu/Fa'asiila), the Head of the Hamlet, and other witnesses. The Village government then instructed the Village Office (customary authorities) to summon both parties (the offenders and the victim) to attend discussions to settle the crime of domestic abuse after verifying that the complaint had correct evidence. 2020 saw the perpetrator punished in line with the village of Bonia Hilisimaetano's customary law, which called for giving three pigs and Rp 3,000,000 (three million rupiah) to the victim's family as well as the village government. The victim was not hospitalized. This punishment, however, differs from that meted down to the offenders of the same offense in 2012 in that the victim was admitted to the hospital in addition to receiving Rp 3,000,000 and 1 (one) pig 4 alisi. It is intended that the penalties would serve as a deterrence to the offender and provide justice to the victim.